First-principles calculations to investigate structural, electronic, optical, and elastic properties of RbBaX (X= P, As, Sb, Bi) alloys for optoelectronic applications - Jamil, Aurwa; Dawood, Hafsa; Aslam, Rimsha; Ghodhbani, Refka; Hussien, Mohamed; Yaqoob, Umbreena; Rasul, Muhammad Nasir (The Journal of physics and chemistry of solids, 2025)
Half-Heusler alloys are renowned for their exceptional properties, making them a compelling subject of research across diverse fields such as optoelectronics and renewable energy. This study scrutinizes the RbBaX (X = P, As, Sb, Bi) compounds using first-principles calculations built upon density functional theory via generalized gradient approximation and modified Becke-Johnson potentials schemes. The compounds confirm the thermodynamic and mechanical stability with lattice constants 7.8135 Å, 8.0009 Å, 8.4225 Å, and 8.5648 Å of RbBaX (X = P, As, Sb, Bi) respectively. The electronic properties revealed band gaps of 0.9768 (2.4567), 0.7739 (2.1084), 1.0471 (2.1523), and 0.5852 (1.43864) eV for RbBaX (X = P, As, Sb, Bi) via GGA (mBJ) potentials, indicating their potential for optoelectronic applications. The molecular orbital analysis shows p-type interactions in the HOMO and s-type interactions in the LUMO, while the –COHP analysis highlights the strongest anti-bonding interactions at X–Rb sites. The computed optical properties including dielectric function ɛ(ω), effective electron number (Neff), absorption coefficient α(ω), optical conductivity σ(ω), refractive index n(ω), extinction coefficient k(ω), reflectivity R(ω), and energy loss function L(ω) have been extensively analyzed, underscoring their suitability for intermediate solar band energy harvesting and sensor applications. Additionally, the physico-mechanical characteristics and anisotropic behavior in 2D and 3D crystallographic planes demonstrate the material's robustness. The comprehensive findings highlight the significant potential of RbBaX (X = P, As, Sb, Bi) compounds in advanced technological applications, particularly in solar energy, sensing devices, renewable energy technologies, and optoelectronic applications. [Display omitted] •Investigation of physical properties of RbBaX (X = P, As, Sb, Bi) compounds via DFT.•RbBaX (X = P, As, Sb, Bi) have been found structurally, lattice dynamically, and mechanically stable.•HOMO and LUMO depict p-type and s-type interaction respectively.•RbBaX (X = P, As, Sb, Bi) have demonstrated an indirect band gap semiconducting behavior.•RbBaX (X = P, As, Sb, Bi) can be good candidates for optoelectronic applications.